ATM networks for multimedia / Syam Zakiril Ikmar Khishara - Khishara, Syam Zakiril Ikmar (1998)
This paper is a project report on the introduction of ATM technology application in networked multimedia environment. For this paper, the concepts of ATM technology, ATM networking for multimedia and networked multimedia applications will be described. ATM is a set of international standards for high-speed digital networks. With ATM, massive amounts of multimedia applications such as data, voice, image and video information can be send simultaneously over a single network with a speed up to a thousand times faster than is possible today. For the purpose of performance evaluation, a simulation model of a typical ATM networked multimedia and its analysis will be presented. This network consists of real-time and non real-time multimedia applications that will be conveyed either as CBR or VBR traffic. The simulation software to be used for modelling and analysis is COMNET III Release l.li.